2020
DOI: 10.3390/rs13010096
|View full text |Cite
|
Sign up to set email alerts
|

On the Potential of Improving WRF Model Forecasts by Assimilation of High-Resolution GPS-Derived Water-Vapor Maps Augmented with METEOSAT-11 Data

Abstract: Improving the accuracy of numerical weather predictions remains a challenging task. The absence of sufficiently detailed temporal and spatial real-time in-situ measurements poses a critical gap regarding the proper representation of atmospheric moisture fields, such as water vapor distribution, which are highly imperative for improving weather predictions accuracy. The estimated amount of the total vertically integrated water vapor (IWV), which can be derived from the attenuation of global positioning systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…As these radio signals propagate through the earth's atmospheric layers (mainly along the troposphere and ionosphere) they are significantly affected by the physical characteristics of these layers and, thus, the propagation speed is reduced [43]. The extent of the delay depends largely on the temperature, pressure, and water vapor distribution, which differ considerably in space and time [44][45][46][47][48][49]. In contrast to the nondispersive tropospheric interaction, the speed at which radio signals propagate at a particular height through the ionosphere is constrained by the free electron density concentration in surrounding areas [50], and the radio signal phase speed is essentially increased by the existence of free electrons.…”
Section: Ionospheric Total Electron Content (Tec)mentioning
confidence: 99%
“…As these radio signals propagate through the earth's atmospheric layers (mainly along the troposphere and ionosphere) they are significantly affected by the physical characteristics of these layers and, thus, the propagation speed is reduced [43]. The extent of the delay depends largely on the temperature, pressure, and water vapor distribution, which differ considerably in space and time [44][45][46][47][48][49]. In contrast to the nondispersive tropospheric interaction, the speed at which radio signals propagate at a particular height through the ionosphere is constrained by the free electron density concentration in surrounding areas [50], and the radio signal phase speed is essentially increased by the existence of free electrons.…”
Section: Ionospheric Total Electron Content (Tec)mentioning
confidence: 99%
“…In the past three decades, GNSS-derived PWV has been compared to radiosonde measurements, radiometers, sun photometers and reanalysis products which resulted in an RMSE ranging from 1 to 3 mm, thus ensuring its importance as an atmospheric remote sensing platform (Li et al, 2003;Van Baelen et al, 2005;Wang et al, 2007;Pérez-Ramírez et al, 2014;Wang et al, 2017a). Furthermore, Leontiev et al (2021) showed that assimilating the GNSS-derived PWV maps into modern weather numerical prediction models (e.g., WRF) lowered the RMSE by more than 30% when comparing to radiosonde measurements.…”
Section: Global Navigation Satellite System Meteorologymentioning
confidence: 99%
“…Furthermore, Leontiev et al . (2021) showed that assimilating the GNSS‐derived PWV maps into modern weather numerical prediction models (e.g., WRF) lowered the RMSE by more than 30% when comparing to radiosonde measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies also have proven that assimilation of external water vapor data, for example, GNSS PWV and Interferometric synthetic aperture radar (InSAR) PWV, into the WRF model can improve the WRF model's performance in forecasting PWV (Leontiev et al, 2020;Mateus & Miranda, 2022;Mateus et al, 2021;Xiong et al, 2020). For example, Leontiev et al (2020) assimilated PWV data from the Global Positioning System (GPS) PWV maps augmented by the Meteosat satellite imagery data into the WRF model to improve its PWV forecasting accuracy in Israel and neighboring areas. Their results indicated that the WRF model can forecast PWV with a root mean square error (RMSE) of 2.5-2.6 kg/m 2 for the forecast length of 3-12 hr.…”
Section: Introductionmentioning
confidence: 99%